2017
DOI: 10.1103/physreve.95.012403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lipid rafts on theT-cell-receptor and peptide-major-histocompatibility-complex interactions under different measurement conditions

Abstract: The interactions between T-cell receptor (TCR) and peptide-major-histocompatibility complex (pMHC), which enable T-cell development and initiate adaptive immune responses, have been intensively studied. However, a central issue of how lipid rafts affect the TCR-pMHC interactions remains unclear. Here, by using a statisticalmechanical membrane model, we show that the binding affinity of TCR and pMHC anchored on two apposing cell membranes is significantly enhanced because of the lipid raft-induced signaling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…To consider the tendency for lipid rafts to coalesce due to their hydrophobic mismatch with the membrane matrix, we assume a contact energy u for nearest-neighbor raft patches. The total raftraft contact energy is then described by (Li et al, 2017b)…”
Section: Model and Methodsmentioning
confidence: 99%
“…To consider the tendency for lipid rafts to coalesce due to their hydrophobic mismatch with the membrane matrix, we assume a contact energy u for nearest-neighbor raft patches. The total raftraft contact energy is then described by (Li et al, 2017b)…”
Section: Model and Methodsmentioning
confidence: 99%
“…Moreover, experimental results from the adhesion frequency and thermal fluctuation assays using a micropipette indicate that disrupting the membrane microdomains, often termed lipid rafts, with methyl-β-cyclodextrin reduces the binding affinity of TCR and pMHC (Huang et al, 2010). To illuminate the mechanism underlying the raft-regulated receptorligand interaction, Li et al developed a multicomponent membrane adhesion system in the framework of classical statistical mechanics and systematically studied the interplay between the receptor-ligand interaction and lipid raft (Li et al, 2017a;Li et al, 2017b;Li et al, 2018;Li et al, 2020;Li et al, 2021d;Li et al, 2021e;Li et al, 2021c;Li et al, 2022;Li et al, 2023). They found that lipid rafts enhance the receptor-ligand binding affinity, consistent with the experimental results, and the receptor-ligand binding in turn contributes to the raft coalescence.…”
Section: Discussionmentioning
confidence: 73%
“…The on-rate k on and off-rate k off describe the velocity of receptor-ligand complex formation and dissociation, respectively. The binding affinity K quantifies the receptor-ligand binding strength (Li et al, 2017a;Li et al, 2017b;Overall et al, 2020;Li et al, 2023). Establishing the relationship between receptor-ligand binding kinetics and cellular responses is bound to help pharmaceutical development greatly.…”
Section: Introductionmentioning
confidence: 99%
“…The association of receptor and ligand with lipid rafts is taken into account by introducing the coupling energy, i.e., the raft affinity to adhesion proteins. Simulation results from this multicomponent membrane system with biologically relevant parameters consistently show that the preferential partitioning of membrane-anchored receptor and ligand proteins in the lipid rafts significantly increases the binding affinity of those proteins, depending strongly on the properties of lipid rafts such as area fraction, size and the affinity of rafts to the proteins ( Li et al, 2017b ; Li et al, 2017c ; Li et al, 2018a ; Li et al, 2021d ). This enhancement is traced back to the entropy gain of the membranes resulting from raft-induced protein aggregation.…”
Section: Protein-membrane Interactionmentioning
confidence: 77%